Uso de métodos baseados em laser para caracterização da matéria orgânica em solos - Tozo, Marcelo Larsen de Lima (Universidade Federal de São Carlos, 2022)
The growing interest in biogeological carbon sequestration to avoid or offset CO2 emissions, mainly in the interest of generating carbon credits, has stimulated the need to develop monitoring approaches by companies and agricultural producers. Allied to this, the understanding of the molecular structure of organic carbon in soils (COS) and the external factors (pH, granulometry, degree of humification, organo-mineral association) have been considered criteria to predict the rotation of carbon in soils. Research on laser-based spectroscopic techniques (specifically laser-induced breakdown spectroscopy – LIBS and laser-induced fluorescence spectroscopy – LIFS) has become prominent in recent years for real-time characterization of soil properties, due to its versatility and speed. in carrying out analyzes and generating results. In the study of soils collected on a farm located in the city of São Jorge do Ivaí, Paraná, the use of LIFS allowed the characterization of organic matter and its lability, as a function of depth (00-05, 05-10, 10-20, 20-30, 30-40, 40-60, 60-80, 80-100cm) and the collected area (agricultural area and native forest), based on the humification index – HLIFS – calculated. It was observed that the calculated index is higher in the area of ​​agricultural production in relation to the native forest, however in both areas, the value of HLIFS is increasing along the soil profile. In addition, the use of LIBS showed promising results in the quantification of COS, obtaining good correlation with reference techniques (r > 0.89) and low average error of calibration and prediction of carbon content (both smaller than 0.30 % C).
Use of laser-based methods for characterization of organic matter in soils
Keywords: Carbono orgânico em solos; Matéria orgânica em solos; Grau de humificação; LIBS; LIFS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE